Answer:
1/-21
Step-by-step explanation:
Step 1: Simplify both sides of the equation.
17
4
x+
−1
12
=6x
Step 2: Subtract 6x from both sides.
17
4
x+
−1
12
−6x=6x−6x
−7
4
x+
−1
12
=0
Step 3: Add 1/12 to both sides.
−7
4
x+
−1
12
+
1
12
=0+
1
12
−7
4
x=
1
12
Step 4: Multiply both sides by 4/(-7).
(
4
−7
)*(
−7
4
x)=(
4
−7
)*(
1
12
)
x=
−1
21
Answer:
when high-energy particles from the Sun bounce off Earth’s magnetic field
Answer:
the answer is : 2557421289
Hello:
<span>Use De Moivre’s Theorem :
</span>(3(cos27 +isin27)^5 = 3^5( cos(27 × 5) +isin(27 × 5))
= 3^5 ( cos(135)+i sin(135))
= 3^5(-√2/2+i √2/2)
because : cos(135) = -√2/2 and sin(135) = √2/2
(3(cos27 +isin27)^5 = (- 3^5√2/2)+ i ( 3^5√2/2) ...(form : a+ib when
a= (- 3^5√2/2) and b = ( 3^5√2/2)
Please include the graphs!!!!!